The Effect Of Project-Based Learning (PBL) Toward Students’ Ability In Writing Narrative Text At SMP Swasta Gajah Mada - Michael Jomat; Yessy Octaviana; Lastri Wahyuni Manurung (Sean Institute, 2024)
The objective of this research is to examine the narrative writing skill for ninth-grade students at SMP Swasta Gajah Mada is significantly impacted by using of Project-Based Learning (PjBL). The study used a quasi-experimental design that included pre-test and post-test with two groups: an experimental group and a control group. Examining whether students' writing abilities increase when project-based learning is implemented is the study's main goal. There were fifteen students assigned to each group (IX A and IX B) at SMP Swasta Gajah Mada, for a total of thirty students engaged in the study. Participants in the data collection process were given written tests. The results of this study show that project-based learning have a beneficial effect on ninth-grade students’ ability to write narratives at SMP Swasta Gajah Mada. The fact that students in the experimental group scored higher on average once project-based learning was implemented lends credence to this. In addition, the data gathered for this research show a normal distribution. Based on the analysis conducted by using T-test was gotten that T-count = 3,28 at significant level α = 5%, dk (n-1) = (15-1) = 14, so, T-table = 1,76. It could be concluded that T-count > T-table (3,28>1.76). It implied that Ha had been accepted and Ho had been denied. It claimed that the skills of the students before and after using the project-based learning teaching approach differed significantly.